2016
DOI: 10.21767/2473-6457.100004
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Assessment in Water,Sediments and Some Organs of Oreochromis niloticus under the Impact of Sewage Water

Abstract: The present work, aimed to estimation the physicochemical characters of water and metals Aluminum (Al), Chrome (Cr), Manganese (Mn), Iron (Fe), Cobalt (Co), Nickel (Ni), Copper (Cu), Zinc (Zn), Selenium (Se), Cadmium (Cd) and Lead (Pb) accumulation in sediments and different fish organs (gills, intestine, kidney, liver, muscles, ovary, testis and skin) of Oreochromis niloticus, which collected from sewage water in El-kharja, New Valley, Egypt using inductively coupled plasma mass spectrometry (ICP-MS).The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…However Co than Se was the lowest one. Similar to our results, Omar, Zaghloul [37] and Ibrahim, Wassif [22] who found highly precipitation of heavy metals concentration from water column sediment samples.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However Co than Se was the lowest one. Similar to our results, Omar, Zaghloul [37] and Ibrahim, Wassif [22] who found highly precipitation of heavy metals concentration from water column sediment samples.…”
Section: Discussionsupporting
confidence: 92%
“…Also, Kaoud and El-Dahshan [40] reported that Cd and Cu concentrations were the highest in liver. The high Zinc accumulation in liver was in agreeing with Ibrahim [39], El-Naggar and Tayel [41], Ibrahim and Omar [42]; Ibrahim, Wassif [22]. Ibrahim [39] also, found that Fe and Ni accumulation in liver as a target organ of Oreochromis niloticus.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations